Survey of security challenges in university libraries in Southwest Nigeria (2013)
This study investigates security challenges in university libraries in Southwest Nigeria. Questionnaires and interviews were used to collect data for the study. Findings from the study revealed that university libraries in Southwest Nigeria are confronted with security challenges. The challenges include noise making through the use of cell phone, theft, mutilation, and defacement of library materials and hiding of book to prevent other users from having access to them. The study also found that textbooks, serial publications, and reference materials were the materials highly susceptible to abuse by users. The problems are attributed to factors like a harsh economic situation that makes it difficult for library users to buy books and ineffective library security systems. The study recommended adequate and effective security through recruitment, training, and retraining of security personnel; purchase of multiple copies of materials in high demand; provision of photocopying services; adequate training and education for library staff and users on the effects of crime on library services; and tough punishment for perpetrators of library crimes.